Microstructure and Mechanical Properties AlSi7Mg Alloy with Sr, Al and AlSi7Mg - Lipinski, Tomasz (Manufacturing Technology Journal, 2024)
Strength and malleability are important reasons for increasing applications of Al-Si alloys. Mechanical properties of Al-Si cast alloys depend not only on chemical composition but, more importantly, on microstructural features such as morphologies of dendritic α-rich in Al, eutectic β-rich in Si particles and other intermetallics that are present in the microstructure. The microstructure of an unmodified hypoeutectic AlSi7Mg alloy is responsible for the alloy's low strength parameters, and it limits the extent of practical applications. The mechanical properties of hypoeutectic silumins can be improved through chemical modification as well as traditional or technological processing. The improvement in mechanical properties generally has been attributed to the variations in the morphology and size of the eutectic silicon phase particles. This study presents the results of modification of an AlSi7Mg alloy with Sr, Al+ 10% Sr alloy and AlSi7Mg + 10% Sr master alloy. The tests were carried out on modified primary silumin alloy obtained at slow and fast cooling. Modifying additives in granular form and in the form of a rod were used. All additions were introduced into the alloy in an amount that guaranteed a constant strontium contribution to the modified alloy. The influence of the analyzed modifiers on the microstructure and mechanical properties of the processed alloy was presented in graphs. The modification of a hypoeutectic AlSi7Mg alloy improved the microstructure and alloy's properties. The results of the tests indicate that the microstructure and mechanical properties of the modified alloy are determined by the cooling rate of the modifier and its form. Higher parameters were obtained after modification of the AlSi7Mg alloy with a master alloy composed of Sr and AlSi7Mg alloy produced by rapid cooling and introduced in granular form.
Keywords: Silumin; Modification; Strontium; Mechanical properties